Detection of Babesia spp., Theileria spp. and Anaplasma ovis in Border Regions, northwestern China. Issue 6 (22nd June 2018) - Song, R.; Wang, Q.; Guo, F.; Liu, X.; Song, S.; Chen, C.; Tu, C.; Wureli, H.; Wang, Y.
Summary: Babesia spp., Theileria spp. and Anaplasma ovis are important intracellular agents that are transmitted by tick bites. However, Babesia spp., Theileria spp. and A. ovis in ticks have not been systematically reported along the border of northwestern China. In this study, a total of 1, 084 adult ticks, including 134 Haemaphysalis punctata, 337 Hyalomma asiaticum, 233 Dermacentor nuttalli, 69 Rhipicephalus turanicus and 265 Dermacentor marginatus were collected from 11 counties or cities of Xinjiang Uygur Autonomous Region. The ticks were identified from morphological and molecular characteristics. Two fragments of 18S rRNA gene were used to determine the species level of Babesia and Theileria . Msp4 gene encoding major surface protein 4 was used to determine A. ovis . Of the 1, 084 samples, five species of Babesia ( B. occultans, B .  caballi, B .  motasi, B .  major and Babesia sp. detected in this study), two kinds of Theileria ( Theileria ovis and Theileria sp. detected in this study) and A. ovis with six phylogenic branches were detected in the border of northwestern China. Babesia occultans, first found in China, was first molecularly detected in D. nuttalli . Babesia caballi and Babesia sp. detected in this study were first molecularly detected in Hy. asiaticum . Genotype III of A. ovis was predominant in the border regions of northwestern China.